Pengembangan Media Permainan Monopoli Tajwid Dalam Pembelajaran Al-Qur’an Hadist Kelas V di Madrasah Ibtida’iyah Salafiyah Gringsing - Mubarok, Fatih; Martanti, Fitria; Ulumuddin, Imam Khoirul (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
Monopoly Game Learning Media is a learning media used by teachers to deliver a material, the Monopoly Game learning media itself is a game used to support learning and make students more active in learning. The purpose of this study was to determine (1) the hypothetical monopoly game media in Tajwid material in class V (2) the validity of the monopoly game media for Tajwid material for class V (3) the practicality of the game media for monopoly Tajwid material for class V students at MI Salafiyah Gringsing Batang Regency This type of research is development research (Research and Development). The method used to analyze data with quantitative descriptive analysis techniques. The learning media development model used is the ADDIE model. The results of the research that has been conducted are (1) validation by Material Experts and Media Experts as follows: the first by Material Experts includes Learning Aspects getting a percentage of 96% in the very good category, content aspects getting a percentage of 96% in the very good category, evaluation aspects getting a percentage of 96% in the good category, getting an average percentage of 96% in the good category, second by Media Experts including Display aspects getting a percentage of 98% in the very good category, usage aspects getting a percentage of 96% in the very good category, getting an average percentage of 97% in the very good category. (2) the results of the trial to assess practicality got an average assessment of 3.5 getting a good or practical assessment.